Akibat Hukum Bug Hunter Yang Melakukan Illegal Access Terhadap Aplikasi (Jurnal Restorative Justice, 2023)
Finding gaps or bugs in a system or application is a positive activity that is very helpful for application owners who benefit from these findings. Bug hunters who have the ethics to report information on bug findings on a system or application but enter the system or application without the permission of the application owner are still a problem. Activities carried out by Bug Hunter who enters the application system without the developer's permission to find bugs or security holes are done intentionally and knowingly. This research uses a normative legal research method which is carried out by searching and examining library materials or secondary data, finding legal rules, legal principles, by collecting legal materials in the form of legal norms and principles which are then analyzed to provide answers related to the legal issues at hand. The intentionality that became the basis for Bug Hunter in carrying out this action is what resulted in Bug Hunter being caught in Illegal Access even though it was based on good ethical motives, the element of intentionality carried out by Bug Hunter and entering the application system without the permission of the application owner is what resulted in Bug Hunter being caught in Illegal Access.